Enabling genuine participation in co-design with young people with learning disabilities. Issue 4 (2nd October 2022) - Raman, Sneha; French, Tara
ABSTRACT: This paper shares key learnings and emerging principles on ways of enabling genuine participation from young people with learning disabilities in co-design. Reviewing previous research focusing on co-design with young people and people with learning disabilities, we highlight key gaps including – a lack of approaches engaging young people with learning disabilities throughout a co-design process; and limited examples of genuine participation focusing on lived experience and engagement in creative and conceptual decision-making. We present our work with young people with learning disabilities to design a game-based learning tool, with a focus on the co-design process. The work illustrates a situated, tailored Participatory Design approach for engaging participants across all stages of co-design. Findings highlight the importance of contextual preparation by embedding in situ to support multi-vocal, multi-method engagement; and asset-based narratives to empower young people and support expression of voice, enabling creativity and conceptual decision-making. Synthesising key learnings and reflections, we present emerging principles underpinned by a rights-based ethos, with an emphasis on creating the right conditions and developing capacities to enable genuine participation.